Generic framing procedure (GFP) the catalyst for efficient data over transport. - Bonenfant, P.; Rodriguez-Moral, A.
We discuss the generic framing procedure (GFP) in the context of emerging nontraditional data over transport applications. Coupled with complementary efforts to define virtual concatenation, automatic link capacity adjustment schemes, and distributed control planes for transport networks, we contend that GFP serves as the catalyst for efficient and standard data over transport service offerings.
Keywords: SONET; Channel capacity; Data communication; Distributed control; Local area networks; Protocols; Synchronous digital hierarchy; Telecommunication control; Telecommunication standards; Wide area networks